Mui Monitoring Analysis (Case Study Of Sharia Hotel, City Of Medan) - Riyan Pradesyah; AL Bara (Proceeding International Seminar of Islamic Studies, 2019)
This study supports the view of the surveillance system carried out by the Indonesian Ulema Council (MUI), in Medan City. Along with the development of the sharia system that is applied to institutions or companies, making the sharia system very attractive to the public, because it has a very large market. The application of sharia principles has now added to the world of tourism, especially in sharia hotels, operating on the basis of sharia principles. Many hotels now apply sharia principles, becoming the principle of society about the purity of sharia principles themselves. To continue to maintain the purity of sharia principles applied in sharia hotels, the role of MUI is very important in the development and supervision of sharia principles in sharia hotels.               This type of research is a qualitative research with descriptive research. To get maximum results, researchers used the interview method for MUI related to the surveillance system conducted by MUI to continue to improve the purity of sharia principles. The author will also discuss the literature on the MUI supervision system related to sharia hotels.